Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Let's tackle the problem step-by-step.
### Step 1: Partial Fraction Decomposition
We need to decompose the integrand into partial fractions.
The integrand is:
[tex]\[ \frac{x^2 - x + 6}{x^3 + 3x} \][/tex]
First, we factor the denominator:
[tex]\[ x^3 + 3x = x(x^2 + 3) \][/tex]
So, we can express the integrand as:
[tex]\[ \frac{x^2 - x + 6}{x(x^2 + 3)} \][/tex]
We assume a partial fraction decomposition of the form:
[tex]\[ \frac{x^2 - x + 6}{x(x^2 + 3)} = \frac{A}{x} + \frac{Bx + C}{x^2 + 3} \][/tex]
Next, we multiply both sides by the denominator [tex]\( x(x^2 + 3) \)[/tex] to clear the fractions:
[tex]\[ x^2 - x + 6 = A(x^2 + 3) + (Bx + C)x \][/tex]
Now we expand and combine like terms:
[tex]\[ x^2 - x + 6 = Ax^2 + 3A + Bx^2 + Cx \][/tex]
[tex]\[ x^2 - x + 6 = (A + B)x^2 + Cx + 3A \][/tex]
We equate the coefficients of the corresponding powers of [tex]\(x\)[/tex] on both sides:
1. For [tex]\(x^2\)[/tex]: [tex]\( A + B = 1 \)[/tex]
2. For [tex]\(x\)[/tex]: [tex]\( C = -1 \)[/tex]
3. For the constant term: [tex]\( 3A = 6 \)[/tex]
From equation (3):
[tex]\[ 3A = 6 \Rightarrow A = 2 \][/tex]
Substitute [tex]\( A = 2 \)[/tex] into equation (1):
[tex]\[ 2 + B = 1 \Rightarrow B = -1 \][/tex]
So, the partial fraction decomposition is:
[tex]\[ \frac{2}{x} + \frac{(-1)x - 1}{x^2 + 3} \][/tex]
[tex]\[ = \frac{2}{x} - \frac{x + 1}{x^2 + 3} \][/tex]
### Step 2: Integrate the Partial Fractions
Now, we integrate each term separately:
[tex]\[ \int \left( \frac{2}{x} - \frac{x + 1}{x^2 + 3} \right) dx \][/tex]
First, integrate [tex]\( \frac{2}{x} \)[/tex]:
[tex]\[ \int \frac{2}{x} dx = 2 \ln |x| \][/tex]
Next, integrate [tex]\( \frac{x + 1}{x^2 + 3} \)[/tex]. Break it into two integrals:
[tex]\[ \int \frac{x + 1}{x^2 + 3} dx = \int \frac{x}{x^2 + 3} dx + \int \frac{1}{x^2 + 3} dx \][/tex]
For [tex]\( \int \frac{x}{x^2 + 3} dx \)[/tex]:
Use the substitution [tex]\( u = x^2 + 3 \)[/tex], then [tex]\( du = 2x \, dx \)[/tex]:
[tex]\[ \int \frac{x}{x^2 + 3} dx = \frac{1}{2} \int \frac{2x}{x^2 + 3} dx = \frac{1}{2} \int \frac{du}{u} = \frac{1}{2} \ln|u| = \frac{1}{2} \ln|x^2 + 3| \][/tex]
For [tex]\( \int \frac{1}{x^2 + 3} dx \)[/tex]:
Recall the integral of [tex]\( \int \frac{1}{x^2 + a^2} dx = \frac{1}{a} \arctan \left( \frac{x}{a} \right) \)[/tex]:
[tex]\[ \int \frac{1}{x^2 + 3} dx = \frac{1}{\sqrt{3}} \arctan \left( \frac{x}{\sqrt{3}} \right) \][/tex]
Combining these integrals, we get:
[tex]\[ \int \frac{x + 1}{x^2 + 3} dx = \frac{1}{2} \ln|x^2 + 3| + \frac{1}{\sqrt{3}} \arctan \left( \frac{x}{\sqrt{3}} \right) \][/tex]
Thus, the integral becomes:
[tex]\[ \int \left( \frac{2}{x} - \frac{x + 1}{x^2 + 3} \right) dx \][/tex]
[tex]\[ = 2 \ln |x| - \left( \frac{1}{2} \ln |x^2 + 3| + \frac{1}{\sqrt{3}} \arctan \left( \frac{x}{\sqrt{3}} \right) \right) \][/tex]
[tex]\[ = 2 \ln |x| - \frac{1}{2} \ln |x^2 + 3| - \frac{1}{\sqrt{3}} \arctan \left( \frac{x}{\sqrt{3}} \right) \][/tex]
### Final Answer
Thus, the partial fraction decomposition of:
[tex]\[ \frac{x^2 - x + 6}{x^3 + 3x} \][/tex]
is:
[tex]\[ \frac{2}{x} - \frac{x + 1}{x^2 + 3} \][/tex]
And the integral is:
[tex]\[ \int \frac{x^2 - x + 6}{x^3 + 3x} dx = 2 \ln |x| - \frac{1}{2} \ln |x^2 + 3| - \frac{1}{\sqrt{3}} \arctan \left( \frac{x}{\sqrt{3}} \right) + C \][/tex]
where [tex]\( C \)[/tex] is the constant of integration.
### Step 1: Partial Fraction Decomposition
We need to decompose the integrand into partial fractions.
The integrand is:
[tex]\[ \frac{x^2 - x + 6}{x^3 + 3x} \][/tex]
First, we factor the denominator:
[tex]\[ x^3 + 3x = x(x^2 + 3) \][/tex]
So, we can express the integrand as:
[tex]\[ \frac{x^2 - x + 6}{x(x^2 + 3)} \][/tex]
We assume a partial fraction decomposition of the form:
[tex]\[ \frac{x^2 - x + 6}{x(x^2 + 3)} = \frac{A}{x} + \frac{Bx + C}{x^2 + 3} \][/tex]
Next, we multiply both sides by the denominator [tex]\( x(x^2 + 3) \)[/tex] to clear the fractions:
[tex]\[ x^2 - x + 6 = A(x^2 + 3) + (Bx + C)x \][/tex]
Now we expand and combine like terms:
[tex]\[ x^2 - x + 6 = Ax^2 + 3A + Bx^2 + Cx \][/tex]
[tex]\[ x^2 - x + 6 = (A + B)x^2 + Cx + 3A \][/tex]
We equate the coefficients of the corresponding powers of [tex]\(x\)[/tex] on both sides:
1. For [tex]\(x^2\)[/tex]: [tex]\( A + B = 1 \)[/tex]
2. For [tex]\(x\)[/tex]: [tex]\( C = -1 \)[/tex]
3. For the constant term: [tex]\( 3A = 6 \)[/tex]
From equation (3):
[tex]\[ 3A = 6 \Rightarrow A = 2 \][/tex]
Substitute [tex]\( A = 2 \)[/tex] into equation (1):
[tex]\[ 2 + B = 1 \Rightarrow B = -1 \][/tex]
So, the partial fraction decomposition is:
[tex]\[ \frac{2}{x} + \frac{(-1)x - 1}{x^2 + 3} \][/tex]
[tex]\[ = \frac{2}{x} - \frac{x + 1}{x^2 + 3} \][/tex]
### Step 2: Integrate the Partial Fractions
Now, we integrate each term separately:
[tex]\[ \int \left( \frac{2}{x} - \frac{x + 1}{x^2 + 3} \right) dx \][/tex]
First, integrate [tex]\( \frac{2}{x} \)[/tex]:
[tex]\[ \int \frac{2}{x} dx = 2 \ln |x| \][/tex]
Next, integrate [tex]\( \frac{x + 1}{x^2 + 3} \)[/tex]. Break it into two integrals:
[tex]\[ \int \frac{x + 1}{x^2 + 3} dx = \int \frac{x}{x^2 + 3} dx + \int \frac{1}{x^2 + 3} dx \][/tex]
For [tex]\( \int \frac{x}{x^2 + 3} dx \)[/tex]:
Use the substitution [tex]\( u = x^2 + 3 \)[/tex], then [tex]\( du = 2x \, dx \)[/tex]:
[tex]\[ \int \frac{x}{x^2 + 3} dx = \frac{1}{2} \int \frac{2x}{x^2 + 3} dx = \frac{1}{2} \int \frac{du}{u} = \frac{1}{2} \ln|u| = \frac{1}{2} \ln|x^2 + 3| \][/tex]
For [tex]\( \int \frac{1}{x^2 + 3} dx \)[/tex]:
Recall the integral of [tex]\( \int \frac{1}{x^2 + a^2} dx = \frac{1}{a} \arctan \left( \frac{x}{a} \right) \)[/tex]:
[tex]\[ \int \frac{1}{x^2 + 3} dx = \frac{1}{\sqrt{3}} \arctan \left( \frac{x}{\sqrt{3}} \right) \][/tex]
Combining these integrals, we get:
[tex]\[ \int \frac{x + 1}{x^2 + 3} dx = \frac{1}{2} \ln|x^2 + 3| + \frac{1}{\sqrt{3}} \arctan \left( \frac{x}{\sqrt{3}} \right) \][/tex]
Thus, the integral becomes:
[tex]\[ \int \left( \frac{2}{x} - \frac{x + 1}{x^2 + 3} \right) dx \][/tex]
[tex]\[ = 2 \ln |x| - \left( \frac{1}{2} \ln |x^2 + 3| + \frac{1}{\sqrt{3}} \arctan \left( \frac{x}{\sqrt{3}} \right) \right) \][/tex]
[tex]\[ = 2 \ln |x| - \frac{1}{2} \ln |x^2 + 3| - \frac{1}{\sqrt{3}} \arctan \left( \frac{x}{\sqrt{3}} \right) \][/tex]
### Final Answer
Thus, the partial fraction decomposition of:
[tex]\[ \frac{x^2 - x + 6}{x^3 + 3x} \][/tex]
is:
[tex]\[ \frac{2}{x} - \frac{x + 1}{x^2 + 3} \][/tex]
And the integral is:
[tex]\[ \int \frac{x^2 - x + 6}{x^3 + 3x} dx = 2 \ln |x| - \frac{1}{2} \ln |x^2 + 3| - \frac{1}{\sqrt{3}} \arctan \left( \frac{x}{\sqrt{3}} \right) + C \][/tex]
where [tex]\( C \)[/tex] is the constant of integration.
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.